Quantitative efficacy of external and internal browpexy performed in conjunction with blepharoplasty. (4th March 2017) - Mokhtarzadeh, Ali; Massry, Guy G.; Bitrian, Elena; Harrison, Andrew R.
ABSTRACT: Browpexy surgery is a minimally invasive surgical adjunct to upper blepharoplasty. The traditional internal (IB) approach is well documented, while the newer external (EB) variant has only recently been described. To date, there is little quantitative data to evaluate the efficacy of either procedure, and no data to compare results between the two. We determine the efficacy of, and compare surgical results between, internal and external browpexy surgery in lifting the central and lateral brow. A 3.5-year retrospective review of patients undergoing internal and external browpexy surgery to assess the amount of central and lateral lift to the brow was performed. Patients undergoing blepharoplasty without brow lift were used as a control group. The Massachusetts Eye and Ear Infirmary FACE-gram program was used to quantify surgical outcome. Ninety-eight patients are included for review, with an average follow-up of 4–5 months. The average elevation in lateral/central brow position was 2.29 mm and 1.47 mm in the IB group, and 2.97 mm and 1.90 mm in the EB group. These were not statistically significant ( p = 0.164, and p = 0.507, respectively). There was a statistically significant elevation in central and lateral brow height for both browpexy techniques and the control group ( p < 0.001). External and internal browpexy surgery afford a similar, and non-statistically different, elevation of the central and lateral brow at 4–5 months. When compared to standalone blepharoplasty (control) the amount of lift for both procedures is statistically significant.